2014
DOI: 10.1002/lary.24816
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells versus bone marrow-derived stem cells for vocal fold regeneration

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 36 publications
(37 reference statements)
1
64
0
3
Order By: Relevance
“…We have conducted a comparative study in which scarred rat vocal folds were treated with a local injection of either BM-MSCs or ASCs. The results showed similar effects on recovery of hyaluronic acid in the vocal fold lamina propria, but ASCs showed greater ability to produce hyaluronic acid synthase and HGF [ 10 ].…”
Section: Autologous Stem Cellssupporting
confidence: 63%
“…We have conducted a comparative study in which scarred rat vocal folds were treated with a local injection of either BM-MSCs or ASCs. The results showed similar effects on recovery of hyaluronic acid in the vocal fold lamina propria, but ASCs showed greater ability to produce hyaluronic acid synthase and HGF [ 10 ].…”
Section: Autologous Stem Cellssupporting
confidence: 63%
“…Numerous previous studies have identified adipose-derived stem cells (ASCs) as a potential stem cell population with proliferation and differentiation ability similar to bone marrow-derived stem cells (BMSCs) [2426]. ASCs are more easily isolated and can differentiate toward the osteogenic, chondrogenic, adipogenic, myogenic, neurogenic and angiogenic lineages [2732].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Hiwatashi et al compared the effects of BM-MSCs and AD-MSCs in combination with atelocollagen for vocal fold scar regeneration. The authors showed that AD-MSCs had more potential in terms of restoration of hyaluronic acid and suppression of excessive collagen deposition (Hiwatashi et al, 2014;Hiwatashi et al, 2016). Both BM-MSCs and AD-MSCs were considered to have similar potential for treating methotrexate-induced pulmonary fibrosis in rat (Fikry et al, 2015).…”
Section: Discussionmentioning
confidence: 99%